2012
DOI: 10.4161/onci.22128
|View full text |Cite
|
Sign up to set email alerts
|

Inefficient boosting of antitumor CD8+T cells by dendritic-cell vaccines is rescued by restricting T-cell cytotoxic functions

Abstract: Dendritic cells (DCs) are powerful activators of primary and secondary immune responses and have promising activity as anticancer vaccines. However, various populations of immune cells, including natural killer cells, regulatory T cells and especially cytotoxic T lymphocytes (CTLs), can inhibit DC function through cytotoxic clearance. Spontaneous tumor-specific CTL responses are frequently observed in patients before immunotherapy, and it is unclear how such pre-existing responses may affect DC vaccines. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…DC/glioma-specific peptides have been confirmed to be a useful strategy to elicit CTL responses and have been shown to be more effective than other types of DC-based vaccines. Therefore, EGFRvIII peptide-pulsed DCs have distinct advantages over other types of DCs, which provide a robust platform for the generation of large numbers of functional antigen-specific CD8+ T cells [ 46 ]. We found that these CTLs effectively killed EGFRvIII-expressing human glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…DC/glioma-specific peptides have been confirmed to be a useful strategy to elicit CTL responses and have been shown to be more effective than other types of DC-based vaccines. Therefore, EGFRvIII peptide-pulsed DCs have distinct advantages over other types of DCs, which provide a robust platform for the generation of large numbers of functional antigen-specific CD8+ T cells [ 46 ]. We found that these CTLs effectively killed EGFRvIII-expressing human glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of very limited re-stimulation in vivo, OCT4-specific cells are hence likely remain in a slumbered state. Recently, a similar status has been reported for antitumor CTLs capable of inhibiting the expansion of naïve and memory CD8 + T cells, 67 and it has been suggested that a temporary blockade of these perforin-expressing antitumor CTLs could have huge effects on the DC-based enforcement of antitumor responses as well as on the adoptive transfer of T cells equipped with appropriate T-cell receptors.…”
Section: Discussionmentioning
confidence: 54%